2016
DOI: 10.1371/journal.pone.0163632
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor I Does Not Drive New Bone Formation in Experimental Arthritis

Abstract: IntroductionInsulin like growth factor (IGF)-I can act on a variety of cells involved in cartilage and bone repair, yet IGF-I has not been studied extensively in the context of inflammatory arthritis. The objective of this study was to investigate whether IGF-I overexpression in the osteoblast lineage could lead to increased reparative or pathological bone formation in rheumatoid arthritis and/or spondyloarthritis respectively.MethodsMice overexpressing IGF-I in the osteoblast lineage (Ob-IGF-I+/-) line 324–7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…First, low‐intensity constitutive inflammation might be the important driving factor for osteogenesis. Previously, data from animals with CIA were obtained over periods of no longer than 70 days after the last induction; thus, potential subsequent changes in the spine have not been reported . In this study, we extended the observational period to 30 weeks and found that spinal changes began at week 16 and that 40% of the experimental animals had spinal ankylosis at week 30 after induction (Figures A–C).…”
Section: Discussionmentioning
confidence: 67%
“…First, low‐intensity constitutive inflammation might be the important driving factor for osteogenesis. Previously, data from animals with CIA were obtained over periods of no longer than 70 days after the last induction; thus, potential subsequent changes in the spine have not been reported . In this study, we extended the observational period to 30 weeks and found that spinal changes began at week 16 and that 40% of the experimental animals had spinal ankylosis at week 30 after induction (Figures A–C).…”
Section: Discussionmentioning
confidence: 67%